A importância da conservação do meio ambiente cultural para a construção de uma sociedade sustentável : o caso de Laranjeiras/SE - Santos, áurea Jaciane Araujo (2015)
This research versa basically on two points, the conservation of the cultural environment and the development of the municipality of Laranjeiras/SE. The main objective is to examine how the municipal urban and environmental legislation contemplates its tangible and intangible assets with respect to environmental issues. The aim is to verify if the right to the city (LEFEBVRE, 2008) is respected, in order to assist in the understanding of issues relating to the valuation of tangible and intangible heritage for a better sociability. The aim is to finally expand the thinking about the size of environmental protection through a discussion that demonstrates that the artificial and cultural environment are as important as the natural environment in the construction of sustainable societies. The hypothesis is that the strengthening of ties of identity is the basis for the expansion of the vision of the importance of cultural heritage and is a determining factor for the perpetuation of local culture as an asset to be preserved so that future generations can meet you. And, it seems, the municipal legislature in the process of urban laws of Laranjeiras/SE, did not take into account the issues and the complexity of social and environmental problems of the city, so that they do not respond effectively to the demands concerning the preservation, conservation and use of this heritage. Justified this work as a way to prove that when it comes to historic cities, culture should always be the center of attention, so all laws of a city with rich cultural material and immaterial as Laranjeiras is under direct influence of its framework cultural, aimed at environmental development. This research uses the dialectical method, considering the need to address the facts in the political, social and economic context, in order to promote a dynamic and totalizing interpretation of reality (PEREIRA, 2010). To achieve the goal, a bibliographic and documentary survey was conducted, in addition to interviews with several segments at the municipal, state and federal, and several site visits (of the place) aiming at the social reality. This is a qualitative, exploratory and descriptive research with a view to appear problematic. The final text was structured in three parts: Theoretical framework, divided into three (03) chapters. Next is presents the methodology used. Finally, the final chapter with the compilation of collected and processed data on Laranjeiras/SE and the formation of the material and immaterial cultural heritage of the city throughout its history. After which it was concluded that the undoubtedly identity ties are the basis for the expansion of the vision of the importance of cultural heritage and is a determining factor for the perpetuation of local culture as an asset to be preserved so that future generations can meet. The hope is that the results of this research contribute to a comprehensive way of thinking the community of Laranjeiras, so that it can reduce social contrasts as well as strengthen ties between the people and place.